Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Get the answers you need quickly and accurately from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
3n = 18
Step-by-step explanation:
(n + 1) + (n + 3) + (n + 5) = 27
Remove the bracket,
n + 1 + n + 3 + n + 5 = 27
Group like terms,
n + n + n + 1 + 3 + 5 = 27
Add similar elements,
3n + 9 = 27
Substrate 9 from both sides,
3n + 9 - 9 = 27 - 9
Simplify,
3n = 18
Simplify,
n = 6
We got the information, which n = 6.
3n = 3 × 6
= 18
Since all binomials inside the parenthesis are all only being multiplied by one, we can just get rid of all parenthesis forming the equation
n+1+n+3+n+5=27
And now we can combine like terms to form the equation
3n+9=27
Then you would subtract 9 from both sides and then we are left with
3n=18
n+1+n+3+n+5=27
And now we can combine like terms to form the equation
3n+9=27
Then you would subtract 9 from both sides and then we are left with
3n=18
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.